The -α3.7III subtype of α+-thalassemia was identified in China - Bao, Xiuqin; Wang, Jicheng; Qin, Danqing; Zhang, Rui; Yao, Cuize; Liang, Jie; Liang, Kailing; Du, Li (Hematology (Luxembourg), 2022)
The 3.7 kb deletion (-α 3.7 ) in the α-globin cluster, which characterizes α + -thalassemia, has been reported to have a carrier rate of 4.78% in southern China. Three -α 3.7 subtypes have been identified worldwide. However, the -α 3.7 III subtype has not previously been identified in China. Herein, we reported identification of the -α 3.7 III subtype in a Chinese patient. We used gap-PCR and a liquid chip system to detect α-thalassemia mutations. Multiple ligation-dependent probe amplification was performed to detect the large deletion. We finally used Sanger sequencing and single molecule real-time sequencing to characterize and confirm the genotype. The proband, characterized as -α 3.7 III heterozygous, showed microcytosis and hypochromic red cells, with a mean corpuscular volume of 78 fL and mean corpuscular hemoglobin of 25.4 pg. The proband's mutation was inherited from her father, who had normal blood parameters. We first identified the -α 3.7 III subtype in China. Consequently, all -α 3.7 subtypes have now been identified in the Chinese population. Therefore, attention should be paid to -α 3.7 III in clinical prenatal diagnosis, given that commonly used methods such as gap-PCR may lead to misdiagnosis or missed diagnosis.